2019
DOI: 10.1177/1534734619873785
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Drug Therapy for Controlling Pseudomonas aeruginosa and Its Association With Chronic Condition of Diabetic Foot Ulcer

Abstract: Diabetic foot ulcer (DFU) is a major complication of diabetes mellitus, major observations of DFU cases have reported on amputation of foot region, and microbial bioburden during DFU is a major cause that affects healing of the wound regions. Pathogenic microbes are routinely isolated from these wound regions, especially Staphylococcus, Pseudomonas, Klebsiella, and Escherichia coli have been reported, whereas higher prevalence of Pseudomonas species during chronic condition in the deeper part of the wound, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 137 publications
0
11
0
Order By: Relevance
“…39 The increased prevalence of MDR has been noted in different studies worldwide. 30,31,40,41 This can be attributed to extensive use of antibiotics, which gives a selective advantage for survival of pathogenic bacterial strains. MDR P. aeruginosa guarded by biofilms that are difficult to penetrate can survive and develop more resistance.…”
Section: Discussionmentioning
confidence: 99%
“…39 The increased prevalence of MDR has been noted in different studies worldwide. 30,31,40,41 This can be attributed to extensive use of antibiotics, which gives a selective advantage for survival of pathogenic bacterial strains. MDR P. aeruginosa guarded by biofilms that are difficult to penetrate can survive and develop more resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of staphylococci and streptococci are found in the environment [ 51 , 52 ]. Fastidious anaerobics (particularly, those belonging to the Clostridiales Genus XI), Corynebacterium spp., and Gram-negative rods are among the bacteria usually found in the same foot ulcers (namely, Klebsiella spp., Acinetobacter spp., Enterobacter spp., P. aeruginosa , and Escherichia coli ) [ 53 , 54 ].…”
Section: Infection Of Dfusmentioning
confidence: 99%
“…Studies have shown that acyl homoserine lactones (AHLs) regulate multiple factors during biofilm formation by Pseudomonas aeruginosa and play a fundamental role in regulating different genes involved in biofilm formation. Therefore, AHL can be used as a therapeutic target to provide a correct path for drug design targeting multidrug-resistant bacteria[ 73 ]. However, in practice, the abuse of antibiotics still frequently leads to the emergence of drug-resistant bacteria.…”
Section: Treatment Of Dfumentioning
confidence: 99%